The new transactional interpretation of quantum mechanics : the reality of possibility - Kastner, Ruth E., 1955- (New York : Cambridge University Press, 2013)
"A comprehensive exposition of the transactional interpretation of quantum mechanics (TI), this book sheds new light on longstanding problems in quantum theory and provides insight into the compatibility of TI with relativity. It breaks new ground in interpreting quantum theory, presenting a compelling new picture of quantum reality. The book shows how TI can be used to solve the measurement problem of quantum mechanics and explain other puzzles, such as the origin of the 'Born Rule' for the probabilities of measurement results. It addresses and resolves various objections and challenges to TI, such as Maudlin's inconsistency challenge. It explicitly extends TI into the relativistic domain, providing new insight into the basic compatibility of TI with relativity and the physical meaning of 'virtual particles'. This book is ideal for researchers and graduate students interested in the philosophy of physics and the interpretation of quantum mechanics"--
Machine generated contents note: Preface; 1. Introduction: quantum peculiarities; 2. The map vs the territory; 3. The original TI: fundamentals; 4. The new possibilist TI: fundamentals; 5. Challenges, replies, and applications; 6. PTI and relativity; 7. The metaphysics of possibility; 8. PTI and 'spacetime'; 9. Epilogue: more than meets the eye; Appendixes; References; Index.
Includes bibliographical references and index.
Keywords: Transactional interpretation (Quantum mechanics); SCIENCE / Quantum Theory